2011
DOI: 10.2217/fvl.11.62
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Dendritic Cells in Shaping the Adaptive Immune Response During Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract disease in young children. Premature infants, immunocompromised individuals and the elderly exhibit the highest risk for the development of severe RSV-induced disease. Murine studies demonstrate that CD8 T cells mediate RSV clearance from the lungs. Murine studies also indicate that the host immune response contributes to RSV-induced morbidity as T-cell depletion prevents the development of disease despite sustained viral replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 70 publications
(187 reference statements)
2
30
0
Order By: Relevance
“…Hematopoietic cells are permissive to RSV and may serve as a reservoir for this virus in vivo (34). Dendritic cells play a central role in shaping the immune response to, and outcome of, RSV infection (35,36). In agreement with previous studies (27), we demonstrate that in human hematopoietic cells, type I IFN responses to RSV are primarily mediated by pDCs and are independent of endosomal TLRs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hematopoietic cells are permissive to RSV and may serve as a reservoir for this virus in vivo (34). Dendritic cells play a central role in shaping the immune response to, and outcome of, RSV infection (35,36). In agreement with previous studies (27), we demonstrate that in human hematopoietic cells, type I IFN responses to RSV are primarily mediated by pDCs and are independent of endosomal TLRs.…”
Section: Discussionsupporting
confidence: 87%
“…Intriguingly, we found pDCs of term neonates to be profoundly impaired in their capacity to produce IFN-a when compared with those of adults, both in response to RSV and in response to a synthetic RIG-I agonist. pDCs are specialized immune cells that infiltrate the lung to produce large amounts of type I IFN in response to viral infection, and they play a pivotal role in the outcome of RSV infection in a mouse model (35,36). In addition, we found the IFN-a production in MNCs in response to RSV Long and a synthetic RIG-I agonist to be lower among children aged 12 mo to , 5 y when compared with the responses among healthy adults.…”
Section: Discussionmentioning
confidence: 73%
“…4B and C). Our studies also observed a decrease in RSV-specific mRNA, as might be expected with a local sensitization (data not shown) [41]. Thus, this response suggests that exogenously added DCs alter immune responses to the virus and resulted in increased pathology via Th2 cytokine overproduction in agreement with other studies [42][43][44][45].…”
Section: Rsv Infection Enhances Allergen Sensitization and Severe Patsupporting
confidence: 92%
“…It is interesting that while an epithelial cell line (HEp-2 cells) released kynurenine in response to IFN-c, this did not occur after RSV infection. As moDCs are critical cells that link innate and adaptive immune responses, including a central role in immune response to RSV [72,73], we focused on moDCs, instead of epithelial cells. Under inflammatory conditions, IDO becomes expressed and activated in dendritic cells [16,17,[69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…Under inflammatory conditions, IDO becomes expressed and activated in dendritic cells [16,17,[69][70][71]. As moDCs are critical cells that link innate and adaptive immune responses, including a central role in immune response to RSV [72,73], we focused on moDCs, instead of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%